CRISPR interference of nucleotide biosynthesis improves production of a single‐domain antibody in Escherichia coli. Issue 12 (29th August 2020) - Landberg, Jenny; Wright, Naia Risager; Wulff, Tune; Herrgård, Markus J.; Nielsen, Alex Toftgaard
Abstract: Growth decoupling can be used to optimize the production of biochemicals and proteins in cell factories. Inhibition of excess biomass formation allows for carbon to be utilized efficiently for product formation instead of growth, resulting in increased product yields and titers. Here, we used CRISPR interference to increase the production of a single‐domain antibody (sdAb) by inhibiting growth during production. First, we screened 21 sgRNA targets in the purine and pyrimidine biosynthesis pathways and found that the repression of 11 pathway genes led to the increased green fluorescent protein production and decreased growth. The sgRNA targets pyrF, pyrG, and cmk were selected and further used to improve the production of two versions of an expression‐optimized sdAb. Proteomics analysis of the sdAb‐producing pyrF, pyrG, and cmk growth decoupling strains showed significantly decreased RpoS levels and an increase of ribosome‐associated proteins, indicating that the growth decoupling strains do not enter stationary phase and maintain their capacity for protein synthesis upon growth inhibition. Finally, sdAb production was scaled up to shake‐flask fermentation where the product yield was improved 2.6‐fold compared to the control strain with no sgRNA target sequence. An sdAb content of 14.6% was reached in the best‐performing pyrG growth decoupling strain. Abstract : Decoupling growth and production is a promising approach to improve cell factory performance. In this study, Landberg et al. inhibit the expression of selected genes in the nucleotide metabolism to stop cell growth and increase the production of a single‐domain antibody. Using proteomics, they show that the growth inhibited cells maintain their capacity for protein synthesis and do not enter stationary phase.